Pelatihan Pendayagunaan Pangan Lokal Pesisir dan Penanaman Pohon Kelor sebagai Pangan Fungsional Pencegah Stunting - Habib Ihsan M.; I Wayan Romantika; Desidarius Bela Dhesa; Ellyani Abadi (Jurnal Kabar Masyarakat, 2026)
Stunting is a national health problem that has not been resolved to date. Training on the use of local coastal food is still rare and the use of yards through planting moringa is also still lacking in coastal areas. The purpose of this community service is to prevent stunting by training to toddler families about the benefits and innovations of local coastal food and planting moringa trees in the Soropia coastal area. The implementation method uses lectures and demonstrations of making fish and moringa chips. Community service has been carried out in Bajoe Village on 35 mothers with toddlers, using booklets and leaflets. The results of the implementation of the activity are knowledge and the media score obtained before health education is 8 and after 10, with a good knowledge achievement of 100%. The results of the training on making moringa chips, there was an increase in skills before was 10 and after training obtained a score of 12, the achievement of skills after being given training was 91.4%. The results of the Wilcoxon sign rank test obtained a p value of 0.000. The conclusion of community service is that there is an increase in the knowledge and skills of mothers who have toddlers in utilizing local coastal food and the availability of moringa trees in the yards of their homes and the Bajoe Village Hall, Soropia Subdistrict.